Microencapsulation of spirulina platensis by spray drying method as a promising alternative for the development of new products / Microencapsulação da spirulina platensis pelo método spray drying como alternativa promissora para desenvolvimento de novos produtos - Oliveira, Thâmilla Thalline Batista de (2020)
A cyanobacterium that has a high protein content, several bioactive compounds in addition to some vitamins has been microencapsulated so that it can be inserted in the development of new products. This cyanobacterium is of the genus Spirulina and the platensis family and its use is related to benefits that aid human health. Microencapsulation for food preparation is a process in which one or more ingredients or additives (core) are coated with an edible capsule. The objective of this work was to apply three procedures for the wall material: maltodextrin, soy lecithin and a combination of both, in the microencapsulation of microalgae Spirulina platensis, using the dry powder production method from drying using atomization or spray drying technique. Tests of wettability, solubility, sedimentation and determination of moisture were performed for all samples. The best results were obtained from the sample with the highest maltodextrin content as a wall material. In this way, it was possible to perform a microencapsulation using a combination of two compounds as a wall material, however, the ideal conditions for this core material and for each encapsulator still need further studies.